Outcomes of posterior malleolar fixation in ankle fractures in a major trauma centre. Issue 4 (April 2021) - Jeyaseelan, Luckshmana; Bua, Nelson; Parker, Lee; Sohrabi, Catrin; Trockels, Amaury; Vris, Alexandros; Heidari, Nima; Malagelada, Francesc
Highlights: This is the largest study to report outcomes of posterior malleolus fixation. It is one of few studies to report validated patient reported outcome measures. The findings support posterior malleolar fracture fixation, which remains a controversial topic in Foot & Ankle trauma. Abstract: Aims: Ongoing controversy exists over the indications and benefits of posterior malleolar fixation in ankle fractures. The aim of this pragmatic study was to evaluate the outcomes of posterior malleolar fracture fixation in ankle fractures in the setting of a major trauma centre. Our hypothesis is that posterior malleolus fixation leads to improved clinical outcomes. Methods: A total of 320 patients were identified with operatively treated ankle fractures involving a posterior malleolus component, at our institution between January 2012 and January 2018, ensuring a minimum 2 year follow-up. Of these patients, 160 had the posterior malleolus fixed as part of their surgery and 160 did not. Patient demographics, surgical details and complications were assessed. The Manchester-Oxford Foot Questionnaire (MOXFQ) was the primary patient outcome measure. Results: Fixation of the posterior malleolus was associated with a statistically significant improvement in patient outcomes. Mean MOXFQ score in the unfixed posterior malleolus group was 24.03 (0 - 62), compared to 20.10 (0 - 67) in the fixed posterior malleolus group ( p = 0.04). Outcomes were worse with increasing size of posterior malleolar fragment. Metalwork-related issues were higher in the posterior malleolus fixed group (24/160 (15%) versus 10/160 (6.2%)) and re-operation rate was double. Conclusion: This study demonstrates that in the practical setting of a major trauma unit, fixation of the posterior malleolar fracture leads to improved patient outcomes but with increased metalwork risks and reoperation rates.